Performing Detailed Diagnostics Using a Hypothesis Driven Approach - Ioana OLARIU; Gheorghe EPURAN (Risk in Contemporary Economy, 2012)
This paper is about understanding through deep market analysis what are the issues and opportunities in distribution. It highlights the detailed hypotheses driven ‘diagnostic’ framework to perform this analysis and shows the selling force role in successfully managing distribution excellence as a change intervention. For each issue we built the most common hypotheses which can conduct to a certain situation and we have highlighted different type of key questions which can describe each hypothesis.